Multiscale characterization of ageing and cancer progression by a novel network entropy measure1. Issue 7 (16th July 2015) - Menichetti, Giulia; Bianconi, Ginestra; Castellani, Gastone; Giampieri, Enrico; Remondini, Daniel
<x xml:space="preserve">Abstract</x> We characterize cancer and ageing cell states with a multiscale network entropy approach, measuring "parameter space" available to the cell.